Herramienta de Visualización, Monitoreo y Gestión de Dispositivos IoT para Infraestructura de la Compañía Evaluada (2023)
This software project arises from the problems faced by a technology company, which due to its exponential growth shows the need to implement its own system for the administration, information management and verification of IoT hardware device services, which they currently hold in each of their clients. Having as objectives to replace manual processes and obtain efficiency in response times of support agents and proportionally comply with the service level agreements agreed during the commercial management.